Recommendations of the Alzheimer's disease-related dementias conference - Montine, Thomas J; Koroshetz, Walter J; Babcock, Debra; Dickson, Dennis W; Galpern, Wendy R; Glymour, M Maria; Greenberg, Steven M; Hutton, Michael L; Knopman, David S; Kuzmichev, Andrey N; Manly, Jennifer J; Marder, Karen S; et al. (Neurology, 2014)
The National Alzheimer's Project Act, signed into law in 2011, mandates a National Plan to Address Alzheimer's Disease that is updated annually. In the Plan, the term Alzheimer disease includes not only Alzheimer disease (AD) proper, but also several specified related dementias, namely, frontotemporal, Lewy body, vascular, and mixed dementia. In response to a specific action item in the 2012 National Plan, the National Institute of Neurological Disorders and Stroke, in collaboration with the National Institute on Aging, convened panels of experts and conducted a 2-day public conference to develop research priorities and timelines for addressing Alzheimer disease-related dementias (ADRD) in 5 topic areas: multiple etiology dementias, health disparities, Lewy body dementias including dementia with Lewy bodies and Parkinson disease dementia, frontotemporal dementia and related tauopathies, and vascular contributions to ADRD. By design, the product was up to 8 prioritized research recommendations in each topic area including estimated timelines from when work on a recommendation is started to completion or to full implementation of an ongoing activity, and recognition of shared research themes across recommendations. These included increased education and training of both researchers and health care professionals, addressing health disparities, fundamental neurobiology research, advanced diagnostics, collaborative biosample repositories, and a focus on developing effective interventions to prevent or treat ADRD by the year 2025 as targeted by the National Plan.